Bladder dysfunction in human T cell lymphotropic virus infection: A prospective cohort study. - José Abraão Carneiro Neto; Cássius José Vitor de Oliveira; Sheila Nunes Ferraz; Mariele Guerra; Lívia Alves Oliveira; Lúcia Passos; Edgar M Carvalho; Paulo Novis Rocha (Public Library of Science (PLoS), 2022)
Background While bladder dysfunction is observed in the majority of patients with human T cell lymphotropic virus type 1 (HTLV-1)-associated myelopathy (HAM), it is also observed in patients who do not fulfill all diagnostic criteria for HAM. These patients are classified as having possible or probable HAM/TSP. However, it remains unclear whether the severity and progression of bladder dysfunction occurs similarly between these two groups. Objective Compare the severity and evolution of bladder dysfunction in HTLV-1-infected patients with possible and definite HAM/TSP. Methods The present prospective cohort study followed 90 HTLV-1 patients with possible HAM/TSP and 84 with definite HAM/TSP between April 2011 and February 2019. Bladder dysfunction was evaluated by bladder diary, overactive bladder symptoms scores (OABSS) and urodynamic studies. Bladder dysfunction progression was defined as the need for clean self-intermittent catheterization (CIC). Results At baseline, nocturia, urgency and OABSS scores were worse in definite compared to possible HAM/TSP patients. The main urodynamic finding was detrusor overactivity, present in 77.8% of the patients with definite HAM/TSP versus 58.7% of those with possible HAM/TSP (P = 0.05). Upon study conclusion, the cumulative frequency of patients requiring CIC increased in both groups, from 2 to 6 in possible HAM/TSP and from 28 to 44 in definite HAM/TSP patients. The estimated time to need for CIC was 6.7 years (95%CI 6.5-7.0) in the possible HAM/TSP group compared to 5.5 years (95%CI 4.8-6.1) in the definite HAM/TSP group. Conclusions Although both groups showed similarities in bladder dysfunction and tended to progress to requiring CIC over time, patients with possible HAM/TSP presented less severe manifestations at baseline and progressed more slowly than those with definite HAM/TSP.